Education about The Utilization of Cassava Starch (Tapioca) for Health and Making Snack - Suprapto; Endang Nur Widiyaningsih; Rima Munawaroh (LPPMPK-Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2022)
Cassava (Manihot utilissima (Pohl.)) is one of the most widely distributed plants in Indonesia, easy to cultivate, obtain and relatively cheap price. Cassava starch is a type of material that is multifunctional as an excipient in the pharmaceutical field, has many benefits for health and is a potential food source for the community. Tapioca starch or cassava starch can be used as filler, binder and disintegrant in tablet and capsule formulations. Colomadu people in general know cassava only as a source of snacks, but do not know the benefits of cassava in the fields of pharmacy, health and nutritional value. The purpose of the service activity is to provide understanding and understanding for the community, especially Kleben, Gedongan, Colomadu Karanganyar on the use of cassava in the pharmaceutical, health and food fields. This dedication method is by way of presentations through power points, discussions and questions and answers. This service involves local community leaders to coordinate and invite the community as objects of service activities and the general public, both teenagers, adults and parents. The results of this service were felt to be very useful for the local community, which was shown by the enthusiasm of the people who came, asked and wanted a follow-up activity in the form of the practice of making various menu recipes that have been explained. This service activity is expected to increase public knowledge about the optimal use of cassava starch in the pharmaceutical, health and food fields. This activity is also expected to be able to open horizons and as a motivation for the community to open up business opportunities for making food from cassava starch (tapioca).